Policy Options for Addressing Health System and Human Resources for Health Crisis in Liberia Post-Ebola Epidemic - Fidel C.T. Budy, MPH (Global Health and Education Projects, Inc., 2016)
Qualified healthcare workers within an effective health system are critical in promoting and achieving greater health outcomes such as those espoused in the Millennium Development Goals. Liberia is currently struggling with the effects of a brutal 14-year long civil war that devastated health infrastructures and caused most qualified health workers to flee and settle in foreign countries. The current output of locally trained health workers is not adequate for the tasks at hand. The recent Ebola Virus Disease (EVD) exposed the failings of the Liberian healthcare system. There is limited evidence of policies that could be replicated in Liberia to encourage qualified diaspora Liberian health workers to return and contribute to managing the phenomenon. This paper reviews the historical context for the human resources for health crisis in Liberia; it critically examines two context-specific health policy options to address the crisis, and recommends reverse brain drain as a policy option to address the immediate and critical crisis facing the health care sector in Liberia.